Proteomic analysis and sperm physiopathology: The two-dimensional difference in gel electrophoresis approach - Vazquez, Monica Hebe (2013)
Two-dimensional (2D) gel electrophoresis coupled with protein identification using mass spectrometry (MS) is a procedure extensively used to obtain a catalog of several thousand proteins in a single gel. These evaluations provide information that complements and extends the results retrieved from messenger RNA (mRNA) profiling using microarray technologies (1). Basically, the first step on the 2D gel electrophoresis analysis is based on protein separation according to [...].